2014
DOI: 10.1038/bjc.2014.311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nodal staging scores for prostate cancer: a proposal for preoperative risk assessment

Abstract: Background:Pelvic lymph node dissection in patients undergoing radical prostatectomy for clinically localised prostate cancer is not without morbidity and its therapeutical benefit is still a matter of debate. The objective of this study was to develop a model that allows preoperative determination of the minimum number of lymph nodes needed to be removed at radical prostatectomy to ensure true nodal status.Methods:We analysed data from 4770 patients treated with radical prostatectomy and pelvic lymph node dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
2
15
1
Order By: Relevance
“…9,10 Given the expected reverse stage migration precipitated by the US Preventive Services Task Force recommendations against prostate cancer screening, the shift towards performing RP on more high-risk patients and the increasing utilization of extended LND, the number of men with pN1 prostate cancer is expected to increase. These temporal trends, along with the unequivocally detrimental impact of LN metastases on survival, 11 make understanding the natural history of and defining the optimal management strategy for pN1 prostate cancer issues of increasing importance.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Given the expected reverse stage migration precipitated by the US Preventive Services Task Force recommendations against prostate cancer screening, the shift towards performing RP on more high-risk patients and the increasing utilization of extended LND, the number of men with pN1 prostate cancer is expected to increase. These temporal trends, along with the unequivocally detrimental impact of LN metastases on survival, 11 make understanding the natural history of and defining the optimal management strategy for pN1 prostate cancer issues of increasing importance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of multiple lymph node metastases has rarely been reported and ranges between 4 and 17% of cases [5]. Moreover, the rate of bilateral lymph node metastases is not reported in modern series [2,3,5,[15][16][17]. A large multicenter retrospective study including an old cohort has shown that in high-risk selected patients with at least 10 nodes removed (median 15), the rate of LNI was 36.1%, which included ROC, receiverreceiver operating characteristic; AUC, area under the curve; pN, pathologic nodal staging status; pN0, absence of nodal metastases; pN1(u), prostate cancer with unilateral metastatic nodes; pN1(b), prostate cancer with bilateral nodal metastases; PSA, prostate-specific antigen; P(p), proportion of biopsy positive cores.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, there are several predictive nomograms, including the Partin nomogram, for preoperative prediction of final pathologic status (i.e., organ-confined prostate cancer, extracapsular extension, seminal vesicle invasion, or LN metastasis) by use of clinical parameters [28][29][30]. In these nomograms, serum PSA, clinical stage, and biopsy findings are usually investigated because they are known to be associated with the final pathologic stage of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%